A Study on the Design Procedure of Three-Dimensional Printable Tactile Graphics for Individuals With Visual Impairments. (July 2022) - Wu, Chih-Fu; Wu, Hsiang-Ping; Tu, Yung-Hsiang; Yeh, I-Ting; Chang, Chin-Te
Introduction: Three-dimensional (3D) printing can be used to produce tactile teaching materials for individuals with visual impairments. Although 3D and 2.5D teaching materials are based on realistic content, no systematic conversion model for 2D materials exists. Here, we combined the previous findings and this study's results and technology to develop procedure recommendations for tactile-graphic design.Methods: We enrolled 19 participants with congenital blindness to identify and name the tactile graphics. The tactile graphic design involved height differences, materials, and operation zone areas. We recorded the identification time, accuracy, and National Aeronautics and Space Administration–Task Load Index assessment performance and conducted a three-way analysis of the variance to investigate the interactions.Results: A larger area resulted in a better performance in seconds; model 3 (high lines and low planes) under large areas obtained the lowest speed and accuracy performances. Large areas were associated with a better intelligent load, physical load, mental load, and self-performance scores. Model 1 (equal line and plane heights) yielded better physical-load performance. Model 3 was found to be superior when thermoplastic elastomers were used under large areas.Discussion: Larger area ratios could increase the identification performance. As model 3 is not recommended, model 1 was found to be better than model 4 (non-operation-guiding zones become planes) in terms of physical load. Model 2 (low lines and high planes) required more time than model 1; hence model 1 is recommended. Fused deposition modeling (FDM) materials such as FDM_TPE (thermoplastic elastomer) increases the identification steps and should not be used first. The FDM_PLA (polylactic acid) platform is inexpensive and easier to operate than stereolithography (SLA) materials such as SLA_ABS (acrylonitrile butadiene styrene); hence FDM_PLA is recommended.Implications for Practitioners: When designing the graphics, a plan view photograph of the object can be obtained for delineating the contours first. Adjustments should be made after confirming the presentation model. The graphic may then be transferred for 3D printing with PLA materials.